Different Patterns of Ecological Divergence Between Two Tetraploids and Their Diploid Counterpart in a Parapatric Linear Coastal Distribution Polyploid Complex - Castro, Mariana; Loureiro, João; Figueiredo, Albano; Serrano, Miguel; Husband, Brian C.; Castro, Sílvia (Frontiers in Plant Science, 2020)
Polyploidization is a widespread mechanism of evolutionary divergence in flowering plants. Ecological divergence of polyploid lineages has been proposed as a key process shaping the distribution of cytotypes in nature (niche shift hypothesis); however, evidence for the role of niche separation in replicated diploid-polyploid species pairs is still needed. This study aimed to assess the role of abiotic factors shaping current cytotype distributions. For that, we examined the distribution and environmental niches of two varieties recognized in diploid-tetraploid Jasione maritima across the species range and within a contact zone on the Iberian Peninsula. We counted chromosomes, screened for ploidy across contact zones and characterized environmental requirements using niche modelling tools. We found that J. maritima var. maritima is composed by diploids with disjunct distribution in the west coast of France and northwest Iberian Peninsula, and by tetraploids in Iberian Peninsula, while var. sabularia is tetraploid. In the Iberian Peninsula, two parapatric contact zones along a linear coastal distribution were detected, one between diploid and tetraploid var. maritima, and the other between tetraploids of the two varieties. Environmental variables of diploid populations from France are distinct from those of southern diploid populations, which are more similar to tetraploids. In general, niche modeling results are congruent with the observed distribution patterns, although the results suggest a wider contact zone between varieties and cytotypes. Tetraploids of both varieties revealed different degrees of environmental divergence in comparison with their diploid counterpart. Tetraploid var. sabularia differed environmentally from diploids suggesting niche divergence. In contrast, tetraploid var. maritima overlapped with diploid environmental niche and currently occupies its entire predicted range, whereas diploids are restricted to northern areas of their suitable environment. Differences in ecological envelopes facilitate the recognition of functional units of biodiversity within polyploid groups, allowing the study of factors related to post-polyploidization divergence. Thus, whereas changes in environmental requirements may have allowed tetraploid var. sabularia to spread in habitats not favorable to diploids, other factors are involved with the distribution of diploid and tetraploid var. maritima.